Functional fusion of living systems with synthetic electrode interfaces - Staufer, Oskar; Weber, Sebastian; Bengtson, C. Peter; Bading, Hilmar; Spatz, Joachim P.; Rustom, Amin (Beilstein Journal of Nanotechnology, 2016)
The functional fusion of “living” biomaterial (such as cells) with synthetic systems has developed into a principal ambition for various scientific disciplines. In particular, emerging fields such as bionics and nanomedicine integrate advanced nanomaterials with biomolecules, cells and organisms in order to develop novel strategies for applications, including energy production or real-time diagnostics utilizing biomolecular machineries “perfected” during billion years of evolution. To date, hardware–wetware interfaces that sample or modulate bioelectric potentials, such as neuroprostheses or implantable energy harvesters, are mostly based on microelectrodes brought into the closest possible contact with the targeted cells. Recently, the possibility of using electrochemical gradients of the inner ear for technical applications was demonstrated using implanted electrodes, where 1.12 nW of electrical power was harvested from the guinea pig endocochlear potential for up to 5 h (Mercier, P.; Lysaght, A.; Bandyopadhyay, S.; Chandrakasan, A.; Stankovic, K. Nat. Biotech. 2012, 30, 1240–1243). More recent approaches employ nanowires (NWs) able to penetrate the cellular membrane and to record extra- and intracellular electrical signals, in some cases with subcellular resolution (Spira, M.; Hai, A. Nat. Nano. 2013, 8, 83–94). Such techniques include nanoelectric scaffolds containing free-standing silicon NWs (Robinson, J. T.; Jorgolli, M.; Shalek, A. K.; Yoon, M. H.; Gertner, R. S.; Park, H. Nat Nanotechnol. 2012, 10, 180–184) or NW field-effect transistors (Qing, Q.; Jiang, Z.; Xu, L.; Gao, R.; Mai, L.; Lieber, C. Nat. Nano. 2013, 9, 142–147), vertically aligned gallium phosphide NWs (Hällström, W.; Mårtensson, T.; Prinz, C.; Gustavsson, P.; Montelius, L.; Samuelson, L.; Kanje, M. Nano Lett. 2007, 7, 2960–2965) or individually contacted, electrically active carbon nanofibers. The latter of these approaches is capable of recording electrical responses from oxidative events occurring in intercellular regions of neuronal cultures (Zhang, D.; Rand, E.; Marsh, M.; Andrews, R.; Lee, K.; Meyyappan, M.; Koehne, J. Mol. Neurobiol. 2013, 48, 380–385). Employing monocrystalline gold, nanoelectrode interfaces, we have now achieved stable, functional access to the electrochemical machinery of individual Physarum polycephalum slime mold cells. We demonstrate the “symbionic” union, allowing for electrophysiological measurements, functioning as autonomous sensors and capable of producing nanowatts of electric power. This represents a further step towards the future development of groundbreaking, cell-based technologies, such as bionic sensory systems or miniaturized energy sources to power various devices, or even “intelligent implants”, constantly refueled by their surrounding nutrients.
Keywords: biointerface; biosensor; energy harvesting; nanoelectrodes; Physarum polycephalum